In vivo characterization of CYP2D6*12, *29 and *84 using dextromethorphan as a probe drug: a case report. (April 2017) - Gaedigk, Andrea; Twist, Greyson P; Farrow, Emily G; Lowry, Jennifer A; Soden, Sarah E; Miller, Neil A
CYP2D6*84 was first described in a Black South African subject, however, its function remains unknown. Astrolabe, a probabilistic scoring tool developed in our laboratory to call genotypes from whole genome sequence, identified CYP2D6*84 in a trio. The father presented with intermediate metabolism when challenged with the CYP2D6 probe drug dextromethorphan (DM/dextrorphan [DX] = 0.0839). Since his second allele, CYP2D6*12, is nonfunctional, the observed activity is derived by CYP2D6*84 . This finding suggests that the allele's hallmark P267H causes decreased activity toward DM and that this allele should receive a value of 0.5 for Activity Score calculations. The mother's DM/DX of 0.0543 was consistent with the decreased activity classification of CYP2D6*29 . The child, a critically ill neonate, was not phenotyped, but predicted to be a normal metabolizer.